Exploring SOD1 gene for the detection of fetal Down syndrome - Karrupiah, Thilakavathy; Rosli, Rozita; Baskaran, T. P. (CIC Edizioni Internazionali, 2008)
Objective: Fetal cells and circulating cellfree fetal DNA increases in the maternal circulation in women carrying trisomy 21 fetus.